HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN CUCI TANGAN PERAWAT DAN BIDAN DI RUMAH SAKIT EMPAT LIMA - Sutanta, Sutanta (Akademi Keperawatan Giri Satria Husada Wonogiri, 2021)
Indicators of good health services, especially in hospitals, are low or no incidence of nosocomial infections. So that it is the obligation of every hospital to make preventive and promotive in an effort to prevent the occurrence of nosocomial infections in its services. One of the efforts to reduce nosocomial infections is to require and monitor compliance with the hand washing of health workers in the hospital work environment. Hand washing compliance certainly cannot be separated from the knowledge obtained by health workers. Nurses and midwives are one of the front lines in providing services in hospitals so that nurses and midwives. So that researchers are interested in examining whether there is a relationship between knowledge level and compliance with clean hand washing. This research is a quantitative study with a cross-sectional method with a sample of 30 respondents using the Kendal-tau statistical test. The result of this study is that there is a relationship between the level of knowledge and compliance with hand washing of nurses and midwives with a correlation of 0.01.